Efficiency evaluation of a photovoltaic system at the Technical Faculty “Mihajlo Pupin” Zrenjanin - Djordjević, Luka; Novaković, Borivoj; Bakator, Mihalj; Ugrinov, Stefan; Nikolić, Milan; Jankov, Stevica (Journal of Production Engineering, 2025)
Solar energy represents a cornerstone of sustainable development, offering a clean and renewable solution to meet growing energy demands while reducing environmental impact. This study evaluates the performance of a 60.9 kWp photovoltaic (PV) system installed at the Technical Faculty “Mihajlo Pupin” in Zrenjanin, Serbia, over the first six months of 2025. The system, comprising 106 monocrystalline modules and a 50kW inverter, was commissioned on January 16, 2025, and integrated into the national grid as a prosumer in April 2025. Monthly data on energy production, consumption, and environmental metrics were collected using a monitoring platform and an on-site meteorological station, capturing global horizontal irradiation, temperature, and sun hours. The analysis focuses on energy efficiency, economic savings, and environmental benefits, with particular attention to the impact of increased solar irradiation and the prosumer framework. These findings provide insights into the system’s contribution to institutional sustainability and its potential as a model for renewable energy adoption in Serbia.